1991
DOI: 10.1002/food.19910350111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on initial bacteria of prawn

Abstract: This study was carried out to evaluate the effect of heat and cold on the microorganisms existing in prawn. Roasting for 5 min, boiling for 10 min and storage at -18 degrees C for 10, 20 and 30 days were applied on raw prawn to study the effect of each treatment on the bacterial load. The average counts of APC (aerobic plate count) at 25 degrees C and 0 degree C, Enterobacteriaceae, Coliforms and Staphylococci were 1.3 x 10(7), 6 x 10(4), 2 x 10(2) and 3 x 10(3) organisms per gram raw prawn sample, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Sedik et al (1991) showed that cooking decreased the total bacteria count and that of Enterobacteriaceae in 3 and 5 logs cycles, respectively. For total viable bacteria, two different plating methods were chosen thereby facilitating the identification of psychrotropic microbiota and those mesophilic species developing during the chilled storage of the shrimp.…”
Section: Microorganismsmentioning
confidence: 98%
See 1 more Smart Citation
“…Sedik et al (1991) showed that cooking decreased the total bacteria count and that of Enterobacteriaceae in 3 and 5 logs cycles, respectively. For total viable bacteria, two different plating methods were chosen thereby facilitating the identification of psychrotropic microbiota and those mesophilic species developing during the chilled storage of the shrimp.…”
Section: Microorganismsmentioning
confidence: 98%
“…Swartzentruber, Schwab, Duran, Wentz, and Read (1980) obtained counts of 4.9 and 5.5 log cfu/g in plate count agar incubated at 30 and 35 C, respectively in frozen in-shell shrimp. Frozen storage of prawn frequently causes a reduction in bacterial population, the reduction being higher the longer the storage time (Sedik, Roushdy, Khalafalla, & Awad, 1991) and as lower the temperature of storage (Riaz & Qadri, 1990). These authors reported a reduction of 3 log units in total counts (PCA at 25 C) in prawns stored for 30 days and frozen at À18 C. Table 1 Analyses of variance of TVB-N in boiled shrimp during 23 days of chilled storage.…”
Section: Microbiological Analysesmentioning
confidence: 99%
“…Shrimp frozen storage has an impact on reducing the number of bacterial populations. The decrease is getting bigger along with the lower the frozen storage temperature and the longer the storage time (Sedik et al, 1991).…”
Section: Microorganism Testingmentioning
confidence: 99%